Prospects of a multipolar international monetary order - Alam Md Whaheed (Nanyang Technological University, 2020)
The US dollar has been the dominant international currency ever since the introduction of Bretton Woods system. It has experienced turmoil periods at different moments but survived. But in the last twenty-five years the US has been undergoing persistent current account deficit and external debts. As the US has been unable to make necessary fiscal adjustments, there has been growing concerns on the future prospects of US dollar as a dominant international currency. On the other hand, since the 2000s the world has been experiencing transformative changes in the economic landscape because of the rapid advances of emerging economies. Because of these developments, a multipolar international currency order would emerge in foreseeable future involving the US dollar, the euro and the renminbi. The US dollar would remain the dominant international currency in the multipolar currency order in this time horizon. The euro and the renminbi would be regional currencies mostly confined in Europe and Asia respectively. For a full blown multipolar international currency arrangement, both the Eurozone and China need to undertake certain reforms. The Eurozone needs to develop a deep and liquid financial market and continue policy supports for upholding its resilience and unity. On the other hand, China needs to make quick reforms in the areas of capital account convertibility, financial liberalization and flexible exchange rate.